The technique SWOT in the elaboration of strategies for teams' management of basketball (Original) (Revista científica Olimpia, 2020)
The strengths, weaknesses, opportunities, threats (SWOT) technique is the most used among the tools of strategic management. In the present investigation, this technique was applied to the 11-12 year-old female basketball team from Bayamo, Granma province. Six strengths, five opportunities, four weaknesses and five threats were determined. It was also found that in the sports team under study there is a predominance of positive factors, so it is recommended to apply offensive strategies. Consequently, with this diagnosis, strategies were developed to lean on strengths, take advantage of opportunities, protect against threats and minimize weaknesses. The strategies applied made it possible to improve the team's leadership and obtain the title of provincial champion in its category.
Keywords: strategic direction; swot technique; management of sports teams; basketball